Estimating the potential health economic value of introducing universal opt-out testing for HIV in emergency departments in Italy - d’Arminio Monforte, Antonella; d’Ettorre, Gabriella; Galardo, Gioacchino; Lani, Enyal; Kagenaar, Eva; Huntington, Susie; Jarrett, James; Ruf, Murad; Ricciardi, Walter (European journal of public health, 2025)
Abstract In Italy, an estimated 13 000–15 000 people have undiagnosed HIV, and in 2020, 60% of new diagnoses were late-stage (CD4 < 350 cells/mm3). In hospitals, including emergency departments (EDs), testing is largely limited to indicator-condition-guided testing (IC), with written consent universally required. We developed a closed-cohort hybrid decision tree–Markov model to compare health economic values of two HIV testing strategies in the ED: (1) universal opt-out and (2) IC (Italian standard of care). Data sources included healthcare costs and HIV public health data, obtained from national reports and published studies. A lifetime time horizon and a National Health Service perspective were used. Primary outcomes were life years, quality-adjusted life years (QALYs), and costs. Universal opt-out testing resulted in better health outcomes at higher costs. For every 10 000 individuals attending ED, opt-out testing resulted in 15.78 additional new HIV diagnoses and 14.47 more people linked to HIV care compared with IC. Prevalence threshold analysis demonstrated that opt-out testing was cost-effective compared to IC when the HIV prevalence was 0.25% or higher, assuming a willingness-to-pay threshold of €30 000/QALY. Universal opt-out HIV testing in the ED could be a cost-effective way to increase the number of new HIV diagnoses and improve HIV health outcomes in Italy. The model may underestimate the full benefits of this strategy as our model did not consider disengaged patients or transmissions averted. Further research using real-world data is needed to verify our findings.